2006
DOI: 10.1177/0829573506298874
|View full text |Cite
|
Sign up to set email alerts
|

Possible Relationships Between Depressive Symptoms and Reading

Abstract: One hundred and fifty-five students (average age of 127 months) were tested using the WRAT-3 reading and arithmetic subtests, the Self-Perception Profile for Children with Learning Disabilities (SPPLD) and the Children’s Depression Inventory (CDI). One year later they were again tested with the same instruments. The authors hypothesised that increases in depressive symptoms would lead to lowered performance in reading and arithmetic, over and above any changes in performance due to self-perceived competence in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…As in NLD, so too in RD research has identified a higher risk of internalizing problems (Maughan & Carroll, 2006), although externalizing disorders, such as ADHD, seem to be the most frequently observed comorbidities (Carroll, Maughan, Goodman, & Meltzer, 2005; Willcutt & Pennington, 2000). Symptoms of anxiety and depression have been reported (Dahle, Knivsberg, & Andreassen, 2011; Stringer & Heath, 2006), consistent with ICD-10 (World Health Organization, 1992), which describes emotional problems, low self-esteem, and problems with peer relationships as being features commonly associated with RD. To give an example, an epidemiological study in the United Kingdom (Carroll et al, 2005) found that 9.9% of children with RD had a comorbid anxiety disorder, indicating a significantly higher prevalence than among children with no literacy difficulties (3.9%).…”
supporting
confidence: 66%
“…As in NLD, so too in RD research has identified a higher risk of internalizing problems (Maughan & Carroll, 2006), although externalizing disorders, such as ADHD, seem to be the most frequently observed comorbidities (Carroll, Maughan, Goodman, & Meltzer, 2005; Willcutt & Pennington, 2000). Symptoms of anxiety and depression have been reported (Dahle, Knivsberg, & Andreassen, 2011; Stringer & Heath, 2006), consistent with ICD-10 (World Health Organization, 1992), which describes emotional problems, low self-esteem, and problems with peer relationships as being features commonly associated with RD. To give an example, an epidemiological study in the United Kingdom (Carroll et al, 2005) found that 9.9% of children with RD had a comorbid anxiety disorder, indicating a significantly higher prevalence than among children with no literacy difficulties (3.9%).…”
supporting
confidence: 66%